PENGEMBANGAN MODUL ELEKTRONIK BERBASIS GUIDED INQUIRY BERBANTUAN LABORATORIUM VIRTUAL PADA MATERI TERMODINAMIKA KELAS XI SMA - Hermawati, Farah Muthi; Purwanti, Popi; Noor, Iman; US, Supardi (Bestari: Jurnal Pendidikan dan Kebudayaan, 2024)
Abstract: 21st-century learning is closely related to the era of technological development of the Industrial Revolution 4.0. Learning using technology will help teachers explain learning material and also help students understand learning material. One of the technological developments in the world of education is the use of digital-based learning media. There are many types of digital-based learning media, one of which is electronic modules. This research aims to develop learning media in the form of electronic modules that are integrated with the syntax of the guided inquiry learning model and assisted by a virtual laboratory in its application. The development electronic module discusses thermodynamics material for class XI high school students. This research uses the ADDIE research method (Analyze, Design, Development, Implementation, and Evaluation) which is limited to the Development stage. The development of electronic modules has been validated by media experts and material experts. The assessment carried out by media experts obtained scores of 82.67% and 88.00% with the title "Very Appropriate" to be used as a learning medium for thermodynamics material. The assessment carried out by material experts obtained scores of 89.33% and 93.33% with the title "Very Appropriate". This research can be developed to a trial stage with class XI high school students to see the influence or effectiveness of learning media on class XI high school students.Â Keywords: electronic module, guided inquiry, virtual laboratory, thermodynamicsÂ Abstrak: Pembelajaran abad 21 sangat berkaitan dengan era perkembangan teknologi revolusi industri 4.0. pembelajaran dengan menggunakan teknologi akan membantu guru dalam menjelaskan materi pembelajaran dan juga membantu siswa dalam memahami materi pembelajaran. Salah satu perkembangan teknologi dalam dunia Pendidikan adalah penggunaan media pembelajaran berbasis digital. Jenis dari media pembelajaran berbasis digital sangatlah banyak, salah satunya adalah modul elektronik. Dalam penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa modul elektronik yang terintegrasi dengan sintaks model pembelajaran guided inquiry dan berbantuan laboratorium virtual dalam pengaplikasiannya. Modul elektronik pengembangan membahas materi termodinamika untuk kelas XI SMA. Penelitian ini menggunakan metode penelitian ADDIE (Analyze, Desain, Development, Implementation, and Evaluation) yang dibatasi sampai tahapan Pengembangan (Development). Modul elektronik pengembangan telah dilakukan uji validasi oleh ahli media dan ahli materi. Penilaian yang dilakukan oleh ahli media didapatkan nilai sebesar 82,67% dan 88,00 % dengan predikat â€œSangat Layakâ€ untuk dijadikan media pembelajaran materi termodinamika. Penilaian yang dilakukan oleh ahli materi didapatkan nilai sebesar 89,33% dan 93,33% dengan predikat â€œSangat Layakâ€. Penelitian ini dapat dikembangkan kembali ke tahap uji coba kepada siswa kelas XI SMA untuk melihat pengaruh atau efektivitas media pembelajaran terhadap siswa kelas XI SMA.Â Kata Kunci: Modul elektronik, guided inquiry, laboratorium virtual, termodinamika